Oscillations in the prefrontal-hippocampal circuit couple to respiration-related oscillations during all phases of a working memory task - Srikanth, Sunandha; Le, Dylan; Hu, Yudi; Leutgeb, Jill K.; Leutgeb, Stefan (Frontiers in Behavioral Neuroscience, 2025)
Oscillatory activity is thought to coordinate neural computations across brain regions, and theta oscillations are critical for learning and memory. Because respiration-related oscillations (RROs) in rodents can be identified in the prefrontal cortex (PFC) and the hippocampus in addition to canonical theta oscillations, we asked whether odor-cued working memory may be supported by both of these two oscillations. We first confirmed that RROs were propagated to the hippocampus and PFC and that RRO frequency spans a broad range that partially overlaps with canonical theta frequency. During all task phases, we found coherence between PFC and hippocampus at the RRO frequency, irrespective of whether RROs and canonical theta oscillations overlapped or differed in frequency. In parallel, there was also high coherence across PFC and hippocampus at theta frequency, except that the coupling at theta was weakest during odor sampling. Therefore, long-range coordination between brain regions occurs at more than one oscillation frequency in a working memory task, but the two types of oscillations did not show evidence of conjunctively supporting working memory.